The Value of P504s, 34βE12, Ki-67 and PSA in Diagnosis and Prognosis of Prostate Cancer - Song, Jin-Qi; Zhou, Ya-Nan; Tu, Gang-Liang; Xu, Hui (Nepalese Journal of Cancer, 2020)
Background: In recent years, the incidence of prostate cancer (PCa) is increasing. Advanced PCa has a poor prognosis and high cost, which seriously affects the quality of life of patients. Therefore, how to improve the diagnosis rate and prognosis of early PCa is the focus of clinical research. This paper aims to investigate the value of  P504s, 34βE12, Ki-67 and prostate-specific antigen (PSA) in the diagnosis and prognosis of PCa.Objective: To investigate the expression of P504s, 34βE12, Ki67 and PSA in prostate tissues and their clinical significance.Methods: Twenty four cases in the study group were selected from PCa confirmed by pathology in the urology department of Chengde Affiliated Hospital from October 2018 to August 2020, and 33 cases of Benign Prostate Hyperplasia (BPH) confirmed by pathology in the same period were selected as the control group. The expression of P504s, 34βE12 and Ki-67 in prostate tissues were determined by immunohistochemistry.Results: The positive expression rates of P504s, 34βE12 and TPSA or F/TPSA in PCa patients were 95.8%, 12.5% and 87.5%, respectively. The positive rates in BPH patients were 9.1%, 93.9% and 27.3%. The difference between the two groups was statistically significant (p